Effectiveness of dialectical behaviour and exposure therapeutic techniques in the treatment of test anxiety among students with learning disabilities in Oyo state, Nigeria (2011)
Students with learning disabilities are faced with cognitive impairment and emotional problems which compound their academic difficulties and general well-being. Prominent among the emotional difficulties is test anxiety which has been noted to play a significant role in students’ achievement. Despite the problems associated with test anxiety, research efforts on students with learning disabilities have been directed towards mainly meeting the academic needs of students with learning disabilities leaving their emotional needs unattended to. Available studies on test anxiety of students with learning disabilities have focused mainly on identification of factors and comparison of test anxiety of students with and without learning disabilities. However there is a dearth of studies on development of therapeutic intervention that can reduce the test anxiety of students with learning disabilities. This study, therefore, examined the effectiveness of two therapeutic intervention strategies: Dialectical Behaviour Therapy (DBT) and Exposure Therapy (ET) in the treatment of test anxiety among junior secondary school students with learning disabilities. The study adopted pretest-posttest control group quasi-experimental design with 3x3x2 factorial matrix. Purposive random sampling technique was used to select 66 participants from three private secondary schools in Ogbomosho, Oyo State. The participants were randomly assigned to two experimental and one control groups. The instruments used were: Pupils Rating Scale (r=0.91); Stanford Achievement Test Series (r=0.72); and Westside Test Anxiety Scale (r=0.44). Seven hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance (ANCOVA), Multiple Classification Analysis (MCA) and Scheffe post hoc test. There was main effect of treatment on test anxiety of the participants (F (2, 47) =21.23; P < 0.05). There were significant differences between DBT (X=25.58) and ET (X=29.92); DBT (X= 25.58) and control (X=36.19); and ET (X=29.92) and control (X= 36.19). The result also indicated that the treatment programme accounted for 42.9% of the total variance of the participants test anxiety. There was, however, no significant main effect of types of learning disabilities (dyslexia, dyscalculia and dysgraphia) on the test anxiety of the participants. No significant main effect of gender on test anxiety of the participants was observed. There were no two-way interaction effects of gender and treatment; treatment and types of learning disabilities; and gender and types of learning disabilities on test anxiety of the participants. The three- way interaction effect of treatments, gender and types of learning disabilities on test anxiety was also not significant. Dialectical Behaviour and Exposure Therapies were effective in reducing test anxiety of students with learning disabilities. It was recommended that conscious efforts should be made by clinical, counselling, and educational psychologists as well as other stakeholders working with students with learning disabilities to adopt these two therapies when handling test anxiety and other related behavioural problems.